2023
DOI: 10.55563/clinexprheumatol/if8nka
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre case-control study evaluating the safety of anti-SARS-CoV-2 vaccines in a cohort of patients with systemic vasculitis

Abstract: ObjectiveData on the safety of anti-SARS-CoV-2 vaccines in patients with rare rheumatic diseases, such as systemic vasculitis (SV), are limited. The aim of this study was to evaluate the occurrence of a disease flare and the appearance of adverse events (AEs) following administration of anti-SARS-CoV-2 vaccine in a multicentre cohort of patients with SV. Methods Patients with SV and healthy controls (HC) from two different Italian rheumatology centres were asked to complete a questionnaire assessing disease fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…8 The safety of different COVID-19 vaccinations, specifically within a vasculitis population, was assessed in a recent case-control study. 9 Of the 57 cases with AAV included in their review, only one case (a 77-year-old male) had a flare of MPA a few days following vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The safety of different COVID-19 vaccinations, specifically within a vasculitis population, was assessed in a recent case-control study. 9 Of the 57 cases with AAV included in their review, only one case (a 77-year-old male) had a flare of MPA a few days following vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…There were no reports of AAV following COVID‐19 vaccination during the phase III clinical trials that formed the basis for Therapeutic Drug Administration approval; however, these studies were not powered to detect such rare adverse effects 8 . The safety of different COVID‐19 vaccinations, specifically within a vasculitis population, was assessed in a recent case–control study 9 . Of the 57 cases with AAV included in their review, only one case (a 77‐year‐old male) had a flare of MPA a few days following vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding these intriguing results, most data from either clinical trials or real-life cohort studies of people with autoimmune diseases do not evidence an increased safety risk after COVID-19 vaccine administration in terms of disease flares or worsening, as shown in Table 6 [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 45 , 46 ]. However, these results may be confounded by concomitant immunosuppressive treatments that limit the magnitude of the immune response to both the vaccine and self-epitopes [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…These events include connective tissue diseases, autoimmune arthritis, myocarditis, and vasculitis [ 3 , 4 ]. On the other hand, anti-SARS-CoV-2 vaccines have been shown to be safe in patients with previously diagnosed autoimmune diseases in both clinical trials and real-life studies [ 5 , 6 , 7 , 8 , 9 , 10 ]. These seemingly contradictory data may be explained by a different pharmacological background of the two cohorts studied (no immunosuppressive therapy in patients with de novo developing diseases).…”
Section: Introductionmentioning
confidence: 99%
“…However, in the current study, no AAV patient experienced a disease flare and kidney function remained stable during follow-up. In a multicenter case-control study of 107 individuals with systemic vasculitis, including 57 AAV patients, Simoncelli et al recently reported only one disease flare after a first mRNA SARS-CoV-2 vaccine dose and no further episodes after the second or third vaccination [ 53 ]. It should be noted that neither the study by Simoncelli et al nor our current study are powered or designed to definitively exclude safety concerns in AAV patients after mRNA vaccination.…”
Section: Discussionmentioning
confidence: 99%